Global greening drives significant soil moisture loss - Yongchang Liu; Zhi Li; Yaning Chen; Liangning Jin; Feng Li; Xuanxuan Wang; Yunxia Long; Chuanxiu Liu; Patient Mindje Kayumba (Communications Earth & Environment)
Abstract Vegetation dynamics, as fundamental terrestrial ecosystem components, regulate precipitation and evapotranspiration, directly affecting soil moisture (SM). However, global greening’s impact on SM (drying or wetting) remains uncertain. Here, we integrate multi-source satellite observations, reanalysis data, and outputs from 12 Earth System Models (ESMs) resampled to a unified resolution (0.25°) to quantify historical vegetation-SM couplings (1982–2020) and assess their future persistence (2015–2100). Results show 49.96% and 38.19% of global vegetated areas exhibit greening-drying patterns, driven primarily by vegetation transpiration, especially in grasslands and cultivated land (42-82% sensitivity). The ESMs predicted that soil dryness is exacerbated by vegetation greening and is expected to continue in the future. Despite uncertainties arising from discrepancies in model parameterizations in ESMs and the limited representation of regional-scale feedback across SM datasets, our study provides a robust and comprehensive assessment of the widespread impacts of global vegetation greening on soil drought. The findings highlight that SM carrying capacity must be prioritized in ecological restoration strategies—particularly in vulnerable semi-arid regions where greening intensifies soil drying (e.g., Central Asia, Central Africa, and southern Australia). Our results provide critical references for guiding sustainable ecological restoration and rational cropland expansion.